If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20r + 13 = -19r + -3r + -9 Reorder the terms: 13 + -20r = -19r + -3r + -9 Reorder the terms: 13 + -20r = -9 + -19r + -3r Combine like terms: -19r + -3r = -22r 13 + -20r = -9 + -22r Solving 13 + -20r = -9 + -22r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '22r' to each side of the equation. 13 + -20r + 22r = -9 + -22r + 22r Combine like terms: -20r + 22r = 2r 13 + 2r = -9 + -22r + 22r Combine like terms: -22r + 22r = 0 13 + 2r = -9 + 0 13 + 2r = -9 Add '-13' to each side of the equation. 13 + -13 + 2r = -9 + -13 Combine like terms: 13 + -13 = 0 0 + 2r = -9 + -13 2r = -9 + -13 Combine like terms: -9 + -13 = -22 2r = -22 Divide each side by '2'. r = -11 Simplifying r = -11
| 8a-15=21-7a | | 2y+17=17 | | 2x^2-5/3x^2-27 | | z/42-69=70 | | 20+s=-15+14-2s | | f(x)=x/(7x-5) | | -26z-0.5=-36z+1.6 | | 2(1)+7=3 | | A=(61)(3) | | 8(x-8)+12=5x | | 3g+2(-6+3g)=1-6 | | 1-7(-2m-3)=8m+1 | | 4x+1-6.2x+2=0 | | 3p+6p+p=81+p | | 7f-16f-16=-6f+17 | | -16+20y=-4y+17+15 | | 3b-2b=-3 | | 5/3•11/3 | | 1.3x-0.02=1.9x+0.16 | | 12r-8-12(r+2)= | | 4x+10=4x-8 | | 8-3(w+3)=4(2w-14) | | 6x+10=(3x+5)2 | | 2xsquare-7x-15=0 | | -10-2d+15=-12-3d | | 4(y+3)=5(y+3) | | 0.2x+0.7=1.2-0.3x | | 56/x=22 | | 6+2x+10=-60 | | f(x)=2x+5givenf(a+5) | | X/2-x/3=11 | | 2x^2+100x-658469=0 |